PENGARUH EDUKASI KESEHATAN REPRODUKSI MENGGUNAKAN MEDIA VIDEO TERHADAP PENGETAHUAN DAN SIKAP CALON PENGANTIN DALAM PERENCANAAN KEHAMILAN SEHAT DI “KUA” CIBADAK LEBAK BANTEN - mawaddah, dina sri; Alamsyah Azis, Muhammad; Susiarno, Hadi (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Prospectives brides are strategic targets groups in improving of pre-conception health. Low pre-pregnancy inflicts pregnancy complications which have mordibity and mortality for mother and fetus, stunting as well. Healthy pregnancy planning have to be done before pregnancy period. Thus, they give positive impacts for the condition of mother and fetus. Intervention for prospectives brides such as giving health education through healthy pregnancy planning video is an attempt of preventing in order to pregnancy complications and stunting do not occur. This research was aimed at analyzing the impact of education media in healthy pregnancy planning through video toward improving of prospectives brides’s knowledge and behavior. This research was a quantitative research (quasi-experimental research) which used pre-test and post-test control group design. The prospectives brides who registered in KUA Cibadak, Lebak regency were selected as sample of this research by using purposive sampling. There were eighteen respondents in each group. The respondents were in the age group of 19-35 years and that their first marriage. Univariate analysis was used to investigate respondents characteristics. Bivariate analysis was used to find out the difference of knowledge and behavior about the education of healthy pregnancy planning in both groups. Then, paired sample t-test, Wilcoxon non-parametric test, and U Mann Whitney test were used in this research. The result of this research showed that video media improved knowledge (p<0,005) and behavior (p<0,005). There was significant improvement of the prospectives brides in video group but it is no higher than leaflet group (p=0,60). The improving of prospectives brides behavior in video group is higher than leaflet group (p=0,009). The conclusion of this research was the education of healthy pregnancy planning through video media improved the prospectives brides’s knowledge and behavior when compared to leaflet media.